Dynamics of structures : Theory and application to earthquake engineeing - Chopra, Anil K. (Noida Pearson, 2020)
Designed for senior-level and graduate courses in Dynamics of Structures and Earthquake Engineering. The text includes many topics encompassing the theory of structural dynamics and the application of this theory regarding earthquake analysis, response and design of structures. No prior knowledge of structural dynamics is assumed and the manner of presentation is sufficiently detailed and integrated, to make the book suitable for self-study by students and professional engineers.
Keywords: Structural Engineering (ME-CE)